Liver transplantation for Hepatocellular Carcinoma: A prognostic model incorporating pretransplant inflammatory cytokines. (May 2022) - Sun, Ruiqi; Zhang, Liang; Yang, Zhentao; Zhou, Ke; Tang, Hong; Zhao, Wentao; Wang, Ning; Yu, Xiaobo; Huang, Yiqian; Xie, Haiyang; Zheng, Shusen; Zhang, Wu
Highlights: Pretransplant serum levels of BLC and IL-12P40 are useful for the early recurrence prediction of HCC patients after liver transplantation. A pretransplant risk assessment model incorporating BLC and IL-12P40 shows excellent efficiency in recurrence prediction of HCC patients. The model could optimize the risk stratification of recurrence in patients exceeding the Milan criteria or AFP model. Abstract: Purpose: Liver transplantation (LT) remains an optimal treatment for selected hepatocellular carcinoma (HCC). Cytokines can be obtained by minimally invasive techniques and are associated with the development of HCC. The purpose of our investigation was to explore the prognostic value of pretransplant serum inflammatory cytokine profiles in HCC patients for LT. Methods: We detected forty inflammatory cytokines in pre-LT serum from 42 HCC patients by using an inflammation-related antibody array. A pretransplant serum inflammatory cytokine-associated risk assessment model (pre-SCRAM) was developed and was validated in an external cohort of 213 HCC patients who underwent LT and were then followed prospectively. Results: The pre-LT factors independently associated with recurrence-free survival (RFS) were as follows: B-lymphocyte chemoattractant (BLC), interleukin (IL)-12p40 and maximum tumor diameter. High IL-12P40 level was associated with a significantly smaller maximum tumor diameter ( p  = 0.021), decreased proportion of nodules ≥ 3 ( p  = 0.001), lower platelet counts ( p  = 0.011) and lower portal vein tumor thrombus ( p  = 0.031). Conversely, recipients with poor BLC level had higher alpha-fetoprotein (AFP) levels ( p  = 0.016). Kaplan–Meier analyses revealed that high pre-LT BLC or IL-12p40 level was associated with superior RFS. The pre-SCRAM stratified recipients into three risk groups: high risk, intermediate risk and low risk. In the validation cohort, for patients in the high, intermediate, and low risk groups, the 3-year RFS rates were 29.3%, 58.7%, and 82.2%, respectively, the 3-year HCC-specific survival rates were 54.5%, 73.8%, and 86%, respectively, and the 3-year overall survival rates were 44.4%, 60.9%, and 79.9%, respectively. The pre-SCRAM model performed well and remained significant in optimizing the risk stratification of recurrence in patients beyond the Milan criteria or the AFP model. Conclusion: Pretransplant cytokine profiles can provide powerful prognostic information in the setting of LT for HCC. A pre-LT risk model incorporating cytokines showed excellent efficiency in recurrence prediction for HCC patients, which could ultimately stratify the prognosis in patients beyond the Milan criteria or the AFP model.